Comparison of tapered-wedge short and standard-length femoral stems in single-stage bilateral direct anterior total hip arthroplasty - UÇAN, VAHDET; UÇAN, VAHDET; EZİCİ, VOLKAN; EZİCİ, VOLKAN; ALIYEV, ORKHAN; ALIYEV, ORKHAN; UZER, GÖKÇER; UZER, GÖKÇER; TUNCAY, İBRAHİM; TUNCAY, İBRAHİM; YILDIZ, FATİH; YILDIZ, FATİH (My University, 2021)
Purpose This study was performed to compare short and standard-length tapered-wedge-type femoral stems in single-stage bilateral total hip arthroplasty (THA) through a direct anterior approach (DAA). Materials and methods The patients were divided into two groups according to their femoral stem types as short tapered-wedge stem and standard-length tapered-wedge stem groups. Outcome parameters were the surgical time, estimated blood loss (EBL), length of stay (LOS), thigh pain, Harris Hip Score (HHS), and visual analog scale (VAS) score clinically, and canal fill ratio (CFR), coronal plan alignment of the stems, subsidence, and postoperative leg length difference (LLD), radiologically. Results The short-stem group and standard-length-stem group consisted of 20 patients (40 hips, mean age 52.0 +/- 14.1) and 22 patients (44 hips, mean age 49.4 +/- 11.9), respectively. There were no significant differences between the groups in terms of mean surgical times (p = 0.6), EBL (p = 0.2), LOS (p = 0.2), the rate of thigh pain (p = 0.4), improvements in HHS (p = 0.4) and VAS scores (p = 0.6), LLD (p = 0.3), amount of subsidence (p = 0.9), and varus or valgus misalignment (p = 0.7). The CFR at the level of the lesser trochanter was significantly higher in the short-stem group (0.79 +/- 0.1) than the standard-length-stem group (0.73 +/- 0.1) (p < 0.01). Conclusion In single-stage bilateral THA through DAA, short, tapered-wedge femoral stems provide similar radiographic and functional results to standard stems at short-term follow-up.